Biosensors: a potential tool for quality assurance and food safety pertaining to biogenic amines/volatile amines formation in aquaculture systems/products - Veluthevar Ramanathan Heerthana; Radhakrishnan Preetha (Wiley Publishing Asia Pty Ltd, 2025)
The present review focuses on the role of volatile amines as a quality indicator which affects the safety and acceptance parameters of the aquaculture products. The nurturing aquaculture requires good aquaculture practice to safeguard aquaculture environment. Particularly, poor water quality of aquaculture systems, changes in storage temperature after harvest and unhygienic handling practices enhance the growth of harmful microbes and thereby magnify the accumulation of biogenic amines (histamines, prolamines cadaverine, putrescine, spermidine, spermine, tyramine and tryptamine) and total volatile basic nitrogen (dimethylamine, trimethylamine and ammonia) content in the aquaculture products. Various conventional and advanced tools used to monitor the aquatic environment/ aquaculture products are discussed in this review. Moreover, this review focuses on the biosensors used for determination of biogenic amines/volatile amines for assuring safety and quality of aquaculture products and aquaculture systems.